2000
DOI: 10.1016/s0896-6273(00)00161-6
|View full text |Cite
|
Sign up to set email alerts
|

PDZ Domain Suppression of an ER Retention Signal in NMDA Receptor NR1 Splice Variants

Abstract: The NMDA receptor NR1 subunit has four splice variants that differ in their C-terminal, cytoplasmic domain. We investigated the contribution of the C-terminal cassettes, C0, C1, C2, and C2', to trafficking of NR1 in heterologous cells and neurons. We identified an ER retention signal (RRR) in the C1 cassette of NR1, which is similar to the RXR motif in ATP-sensitive K(+) channels (Zerangue et al., 1999). We found that surface expression of NR1-3, which contains C1, is due to a site on the C2' cassette, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
292
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(316 citation statements)
references
References 60 publications
23
292
0
1
Order By: Relevance
“…Remarkably, although the K526N mutant did not diminish current, surface expression was reduced by 40% (Figure 3(a ) ). To confirm the impact of K526N in trafficking in mammalian cells, we fused the AB domain to the membrane protein Tac (interleukin-2 receptor α subunit) and monitored surface expression by flow cytometry in HEK293T cells as previously described [15,33,34]. The results confirmed that this mutation caused a reduction in surface expression (Figure 3(b)).
10.1080/19336950.2018.1511512-F0003Figure 3.Surface expression is reduced in K526N and R333Q mutants.
…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, although the K526N mutant did not diminish current, surface expression was reduced by 40% (Figure 3(a ) ). To confirm the impact of K526N in trafficking in mammalian cells, we fused the AB domain to the membrane protein Tac (interleukin-2 receptor α subunit) and monitored surface expression by flow cytometry in HEK293T cells as previously described [15,33,34]. The results confirmed that this mutation caused a reduction in surface expression (Figure 3(b)).
10.1080/19336950.2018.1511512-F0003Figure 3.Surface expression is reduced in K526N and R333Q mutants.
…”
Section: Resultsmentioning
confidence: 99%
“…terminus of NR1 influences intracellular distribution (Ehlers et al, 1995) and surface expression (Okabe et al, 1999;Standley et al, 2000) of NR1/NR2 heteromers. To identify the relevant trafficking signals in NR1 and to minimize effects of NR2 subunits and other NR1 domains, we chose to isolate the contribution of NR1 C-terminal domains using Tac-NR1 chimeras.…”
Section: Discussionmentioning
confidence: 99%
“…1 A). When expressed alone in heterologous cells, these subtypes exhibit differential subcellular localization (Ehlers et al, 1995) and are differentially expressed at the cell surface (Okabe et al, 1999;Standley et al, 2000) (data not shown). To determine which domains of NR1 are responsible for regulating NR1 surface expression, we constructed chimeric receptor molecules consisting of the human interleukin-2 receptor ␣ subunit (Tac) tagged with portions of the intracellular C terminal domain of the NR1 subunit (Leonard et al, 1983;Tan et al, 1998;Craven and Bredt, 2000).…”
Section: Identification Of Trafficking Signals In the C Terminal Domamentioning
confidence: 95%
“…3 Alternative splicing of the C2 cassette regulates cellular trafficking and cell surface expression of the NMDA receptor. [14][15][16] NMDA receptors are predominantly expressed in the postsynaptic membrane where they interact with an intracellularly organized multiprotein complex termed the postsynaptic density (PSD). 17,18 Proteins of the membrane-associated guanylate-kinase family (MAGUKs), a group of PSD-associated proteins characterized by the presence of guanylate kinase, PDZ and Src homology 3 (SH3) protein-interacting domains, function as scaffolding and organizer proteins of the PSD.…”
Section: Introductionmentioning
confidence: 99%